Exploring the emergence of a biojet fuel supply chain in Brazil: An agent‐based modeling approach. Issue 6 (29th January 2019) - Moncada, Jorge A.; Verstegen, Judith A.; Posada, John A.; Junginger, Martin; Lukszo, Zofia; Faaij, André; Weijnen, Margot
Abstract: The aviation industry accounts for more than 2% of global CO2 emissions. Biojet fuel is expected to make an essential contribution to the decarbonization of the aviation sector. Brazil is seen as a key player in developing sustainable aviation biofuels owing to its long‐standing experience with biofuels. Nevertheless, a clear understanding of what policies may be conducive to the emergence of a biojet fuel supply chain is lacking. We extended a spatially explicit agent‐based model to explore the emergence of a biojet fuel supply chain from the existing sugarcane–ethanol supply chain. The model accounts for new policies (feed‐in tariff and capital investment subsidy) and new considerations into the decision making about production and investment in processing capacity. We found that in a tax‐free gasoline regime, a feed‐in tariff above 3 R$/L stimulates the production of biojet fuel. At higher levels of gasoline taxation (i.e., 2.46 R$/L), however, any feed‐in tariff is insufficient to ensure the production of biojet fuel. Thus, at these levels of gasoline taxation, it is needed to introduce regulations on the production of biojet fuel to ensure its production. Given the current debate about the future direction of the biofuel policy in Brazil, we recommend further research into the effect of market mechanisms based on greenhouse gas emissions on the emergence of a Brazilian biojet fuel supply chain. Abstract : The aviation industry accounts for more than 2% of global CO2 emissions. Short‐term options to decarbonize the aviation sector are limited. Biojet fuel is expected to make an essential contribution to the decarbonization of this sector. The aim of this study was to provide insights into what institutional conditions are conducive to the emergence of a biojet fuel supply chain in Brazil. We extended a spatially explicit agent‐based model to explore this phenomenon. We found that the emergence of a Brazilian biojet fuel supply chain hinges on the interaction of the feed‐in tariff and the gasoline tax.